Analysis of Partial Rehabilitation Costs of Earthquake-Resistant Simple House Structures in Bantul Regency - Ibnu Rianto; Rizal Maulana; Sely Novita Sari (G-Tech: Jurnal Teknologi Terapan, 2026)
The vulnerability of simple houses in earthquake-prone areas, particularly those built independently with limitations of key structural elements, demonstrates the need for a measurable and efficient partial rehabilitation approach. Although the reinforcement of earthquake-resistant buildings has been widely studied, the analysis of partial rehabilitation costs separating the calculations on each major structural element is still relatively limited. This study aims to compile an analysis of partial rehabilitation costs on column, ground beam, and ring beam elements by referring to the Unit Price Analysis and the Bantul Regency Standard Unit Price for Materials and Services in 2024. The quantitative method was applied using technical data from the results of MBKM internship activities at the Bantul Regency BPBD, which included the dimensions of structural elements, ironing details, and concrete quality. The calculation of material requirements and costs is carried out separately on each element to obtain a more measurable estimate. The results of the study showed that the cost of rehabilitating columns, ground beams, and beam rings amounted to Rp 14.676.740,54 each, Rp 14.213.412,00, and Rp 13.009.214,44. These findings confirm that differences in dimensions, element functions, and reinforcement methods have a direct effect on the amount of cost. This research contributes in the form of an approach to partial rehabilitation cost analysis that is applicable as a basis for technical decision-making in the planning of simple house reinforcement in earthquake-prone areas.